THE INFLUENCE OF GREEN MARKETING, BRAND IMAGE, AND THE PRODUCT QUALITY TOWARDS CUSTOMER SATISFACTION OF THE BODY SHOP, MANADO TOWN SQUARE - Wenur, Christy; Mandey, Silvya; Tumbuan, Willem A. (Universitas Sam Ratulangi, 2015)
Global warming is a serious problem that is being faced by people around the world. However, global warming is viewed as a specific business opportunity for certain companies. Green marketing strategy is one of the solutions to deal with this business opportunity, especially for companies in the field of cosmetics. The Body Shop is an international cosmetic product retailer that already have a good image and quality while still promoties green marketing strategy. The research objective is to determine the effect of green marketing strategy, brand image and product quality both simultaneously and partially on customer satisfaction as Body Shop Manado Town Square’s consumers. The sample used in this study amounted to 100 people. The analysis method was used multiple linear regression analysis. The results shows that green marketing strategy, brand image and product quality simultaneously influence satisfaction. Partially, green marketing strategy, and product quality significantly influences consumer satisfaction, while brand image partially does not significantly influence customer satisfaction. The Body Shop Manado Town Square should take into account the Green Marketing Strategy, brand image and product quality and to continuously selling products that are environmentally friendly and can be recycled because those product quality are expected by the consumers. Keywords: marketing strategy, brand image, product quality, consumer satisfaction